PENAFSIRAN AYAT-AYAT LARANGAN MEMILIH PEMIMPIN NON-MUSLIM MENURUT SAYYID QUTHB - Erita Erita (Hadharah: Jurnal Keislaman dan Peradaban, 2018)
Non-Muslim leadership becomes a problematic issue in the context of inter-religious relations nowadays, especially for Muslims in conducting religious-social-political relations with non- Muslims. Historically, the issue has been going on for a long time and always invites debates among the Muslim scholars from time to time. In response to this issue, the scholars are divided into two camps, most of them forbid it but others allow. One of the scholars forbidding the choosing of Non-Muslim leadership was Sayyid Quthb, as can plainly be seenon his statement, "Let us led by who are fools as long as they are Muslims rather than led by smart leaders but not Muslims". Hence, this study analyzed Sayyid Quthb’s interpetation regarding to the Qur'anic verses related to the banning of choosing Non-Muslim as a leader. The library research was conducted by gathering data from sources of bibliography related to the topic.  Nevertheless, there are still a handful of liberal Muslim intellectuals who do not possess Shari’a background on the issue of the non-Muslim leadership in the middle of the vast majority of Muslims.